White matter injury following rotavirus infection in neonates: new aspects to a forgotten entity, 'fifth day fits'? - Jung Sook Yeom; Chan-Hoo Park (Korean Pediatric Society, 2016)
That rotavirus infection can cause neurological symptoms in young children has been well established. However, it is surprising why rotavirus infection has been overlooked as a cause of neonatal seizures for many years, despite significant research interest in neonatal rotavirus infection. Neonates are the age group most vulnerable to seizures, which are typically attributed to a wide range of causes. By contrast, because rotavirus infection is usually asymptomatic, it has been difficult to identify an association between this virus and neonatal seizures. The conventional wisdom has been that, although neonates are commonly infected with rotavirus, neurological complications are rare in this age. However, recent studies using diffusion-weighted imaging (DWI) have suggested a connection between rotavirus infection and neonatal seizures and that rotavirus infection can induce diffuse white matter injury without direct invasion of the central nervous system. The clinical features of white matter injury in rotavirus-infected neonates include the onset of seizures at days 4-6 of life in apparently healthy term infants. The recent findings seem to contradict the conventional wisdom. However, white matter injury might not be a completely new aspect of rotavirus infection in neonates, considering the forgotten clinical entity of neonatal seizures, 'fifth day fits'. With increased use of DWI in neonatal seizures, we are just starting to understand connection between viral infection and white matter injury in neonates. In this review, we discuss the historical aspects of rotavirus infection and neonatal seizures. We also present the clinical features of white matter injury in neonatal rotavirus infection.